On the semicontinuity of the solution map to a parametric boundary control problem. (4th March 2017) - Son, Nguyen Hai
Abstract: This paper studies solution stability of a parametric boundary control problem governed by semilinear elliptic equation and nonconvex cost function with mixed state control constraints. Using the direct method and the first-order necessary optimality conditions, we obtain the upper semicontinuity and continuity of the solution map with respect to parameters.